Truth and diversion: Self and other‐regarding lies in dementia care. (2nd October 2021) - Tieu, Matthew
Abstract: When a person with dementia (PwD) makes a specific request or behaves in a particular way that is inappropriate or dangerous and based on a false understanding of reality, there is a particular technique that caregivers may use to try and manage the situation. The technique is known as 'diversion' and it works by affirming the false beliefs and behaviour of a PwD and creating the false impression that their specific request will be fulfilled. It may take the form of an explicit lie or any other communicative response or provision of care that either explicitly or tacitly affirms their false beliefs. It therefore raises the same kind of ethical issues as when lying (or not telling the truth) is done for so called 'therapeutic' purposes. The main type of argument used to justify this so called 'therapeutic lying' is that it is primarily aimed at benefiting the patient rather than the liar. The same kind of argument can be made for diversion, which is that it is primarily aimed at benefiting the PwD by aiming to ensure their safety and well‐being. I argue that insofar as diversion is practiced in this way, it is consistent with the idea of 'person‐centred care' (PCC) and can be ethically justified on those grounds. Therefore, however, we must be wary of situations where diversion is not practiced in this way, where it is primarily aimed at benefiting caregivers or care providers, and thus inconsistent with PCC.